Volume loss fatality model for as-built and retrofitted clay brick unreinforced masonry buildings damaged in the 2010/11 Canterbury earthquakes. (April 2020) - Abeling, Shannon; Ingham, Jason M.
Abstract: Building volume loss can be directly correlated with earthquake fatalities and is therefore considered to be a better damage descriptor for estimating risk to occupants than traditional damage states. Empirical volume loss studies are limited and the study presented herein represents what is likely the first attempt to develop a relationship between commercial unreinforced brick masonry (URBM) buildings attributes, ground motion, and fatalities based on empirical data. Data from two New Zealand earthquakes was utilized to develop a model that predicts the probability of a URBM buildings being in a volume loss damage states (VDS) and the associated probability of an occupant fatality. To demonstrate application of the model, two New Zealand earthquake scenarios are presented and discussed. The model is intended to be applied at a broad scale, to capture an average response over a large number of New Zealand URBM buildings, with applicability to other countries having stocks of comparable URBM buildings.